A note on export redirection: Evidence following the onset of the war in Ukraine - Christian Hutter; Ignat Stepanok; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2023)
The war in Ukraine triggered a global trade shock, with German exports to Russia also collapsing abruptly. Using this break, we analyse whether the exports were redirected to other destinations. We divide the world market into three regions: domestic, eurozone, and the rest of the world (ROW). In a panel model of German industries, we find that higher export exposure to Russia meant lower sales to the ROW after the war began. This was offset by higher sales in the eurozone and domestic markets. The effects occurred quickly but later receded. We find no production decline due to the trade shock. – – Der Krieg in der Ukraine löste einen weltweiten Handelsschock aus, auch die deutschen Exporte nach Russland brachen abrupt ein. Anhand dieses Bruchs analysieren wir, ob es eine Umlenkung der Exporte gab. Wir gliedern den Weltmarkt in drei Regionen: Inland, Eurozone und restliche Welt. In einem Panelmodell im deutschen verarbeitenden Gewerbe stellen wir fest, dass eine höhere Abhängigkeit von Exporten nach Russland nach Kriegsbeginn zu geringeren Verkäufen in die restliche Welt (inkl. Russland) führte. Dies wurde durch höhere Umsätze in der Eurozone und den Inlandsmärkten ausgeglichen. Die Auswirkungen traten schnell ein, ließen aber später nach. Wir stellen keinen Produktionsrückgang aufgrund des Handelsschocks fest.
Keywords: E23; F14; 330; war in Ukraine; export redirection; trade shock; panel model